Change Resistance Toward PSAK 109 - B1034131008, Juni Haryanto (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
Since PSAK 109 are legitimate, most of zakat organization use it as their accounting standard. Eventhough there are number of zakat organization that has use PSAK 109 as their accounting standard, Badan Amil Zakat Nasional (BAZNAS) especially in pontianak still have not use it. Based on that, author are curious about the reason why PSAK 109 have not been aplied yet by BAZNAS. From the curiousity, author do the research about the resistance that happen in BAZNAS that make them still have not applied PSAK 109. The research are done by interview method with BAZNAS leader and employee, author also examine their financial report to find how big different are their report with PSAK 109.Keywords: PSAK 109, Zakat, Alms, BAZNAS, Resistance, Change, Change Resistance, Zakat Accounting.